THE EFFECT OF APPLICATED ASH SAWDUST ON SWAMP LAND (INDRALAYA) FOR VEGETATIVE GROWTH OF RED PEPPER (Capsicum annum L.) VAR. CEMETI - Pratama, Rahmat; Adriyansah, Fikri; Safitri, Ayu; M.S, Rahman Ismail (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
The research